2010
DOI: 10.1016/j.ijimpeng.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Further study on strain growth in spherical containment vessels subjected to internal blast loading

Abstract: Strain growth is a phenomenon observed in the elastic response of containment vessels subjected to internal blast loading, which is featured by the increased vibration amplitude of the vessel in a later stage. Previous studies attributed the strain growth in spherical containment vessels to the beating between two close vibration modes, the interactions between the vessel vibration and the reflected shock waves and the structural perturbation. In this paper, it is shown that nonlinear modal coupling is another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Furthermore, the composite vibration modes, which may be excited by the dynamic unstable vibration (Dong et al 2009), are not considered in the present study, and thus, the dynamic response of the spherical shell is a pure breathing mode vibration. To simplify the analysis, viscous damping is not considered in the model.…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the composite vibration modes, which may be excited by the dynamic unstable vibration (Dong et al 2009), are not considered in the present study, and thus, the dynamic response of the spherical shell is a pure breathing mode vibration. To simplify the analysis, viscous damping is not considered in the model.…”
Section: A C C E P T E D Article In Pressmentioning
confidence: 99%
“…Buzukov 1980). Other possible causes of strain growth in a spherical shell have been discussed in Duffey and Romero(2003) and Dong et al(2009). Numerical analyses also showed that the impulse of the reflected shock waves may reach 50% of the primary impulse (Zhdan 1981), which could enhance M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 97%
“…Compared to the in-plane response of a cylindrical shell which corresponds a plane-strain ring in Li et al [14], the response of a finite-length cylindrical shell with different boundary conditions in the current study is more complicated with the consideration of out-plane response. The material properties and structural dimensions of the cylindrical shell studied in the paper are listed in Tables 1 and 2, respectively.…”
Section: Introductionmentioning
confidence: 90%
“…It has recently been realized that the coupling between the breathing and bending modes, which ASME Journal of Pressure Vessel Technology 4 are excited by the dynamic unstable vibration, is another cause for strain growth of rings (or the in-plane response of cylindrical shells) [14] and spherical shells [15]. However, these conclusions cannot be directly extended to a finite-length cylindrical vessel which is the mostly used type of explosion containment vessels in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the achievements of Kambouchev's research, Vaziri and Hutchinson [10] studied the role of fluid-structure interaction in the design and assessment of sandwich plates subject to shocks. Dong et al [11,12] studied the cause of strain growth in explosive vessel based on the dynamic elastic buckling theory. However, the vibration spectrum analysis of the cylinder shell in the actual operation process is relatively scarce.…”
Section: Introductionmentioning
confidence: 99%